Regulatory barriers in implementing digital health interventions - Antonio Postigo (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2023)
The integration of digital technology into healthcare systems holds promise for improving services in developing countries, especially in remote and underserved regions. However, different types of challenges can impede the implementation and sustainability of digital health initiatives. Technical issues in remote areas, political instability leading to policy-related challenges, and inadequate government support are obstacles to progress. Regulatory barriers can create challenges for the effective implementation of digital health interventions. Inconsistent regulations, outdated guidelines, and legal ambiguities can stifle innovation and escalate costs. Weak or absent regulations on insurance coverage for telemedicine and digital health services further limit financial accessibility. To overcome these challenges, recommendations include the introduction of regulatory sandboxes, pre-certification schemes, and increased international collaboration. These approaches aim to strike a balance between robust regulation and fostering innovation in digital health. The accelerated growth of digital health interventions, exacerbated by the COVID-19 pandemic, underscores the urgent need for proactive and continuous regulatory frameworks. These frameworks play a critical role in ensuring safety, maintaining quality, and promoting equitable access. While some countries have temporarily eased regulations in response to the pandemic, achieving a balanced regulatory approach is essential to address new challenges, potential risks, and disparities in healthcare delivery arising from the evolving digital landscape.
hdl:20.500.12870/6646
Keywords: I18; Q01; 330; Digital health interventions; Health regulation; Regulatory barriers